Inovasi Pelayanan Publik Melalui Jamsostek Mobile (JMO) (Studi Kasus di BPJS Ketenagakerjaan Cabang Rungkut Kota Surabaya) - Samudera, Muhammad Farkhan Dicki; Pertiwi, Vidya Imanuari (Universitas 17 Agustus 1945 Surabaya, 2022)
Public service innovation is a must for the government as a form of adaptation to the development of information technology. One of the government agencies providing public services, namely BPJS Ketenagakerjaan, has launched an innovative JMO application to improve services. The purpose of this study is to find out how public service innovation is through the JMO application at BPJS Employment Rungkut Branch, Surabaya City. The research method used is qualitative data analysis techniques through careful interpretation and verification of each information through primary data and secondary data from interviews, observations, documentation, then analyzed so that conclusions are drawn from research problems. The results of this study indicate that the implementation of JMO service innovations at BPJS Ketenagakerjaan Rungkut Branch Office Surabaya is carried out: 1) institutional leaders provide space to continue to innovate and network relationships to improve JMO services; 2) has implemented transparent and accountable criteria. However, ignoring the criteria for community participation in the suggestion and feedback mechanism; 3) the JMO service data analysis mechanism is still manual so that it is not optimal in solving problems through technology; and 4) JMO service SOPs do not have high flexibility at the branch office level.